Successful thoracic endovascular aortic repair for post-coarctoplasty aneurysm - Sedigheh Saedi (The Egyptian Heart Journal, 2020)
Abstract Background Aortic coarctation is currently treated by both surgical and transcatheter methods. Patients can present with late complication of prior surgical repair including recoarctation and aneurysm formation. There are limited reports on safety and efficacy of thoracic endovascular aortic repair methods (TEVAR) in post-coarctation repair patients. Case presentation We report an adult patient with aortic aneurysm formation following surgical coarctoplasty successfully treated with transcatheter TEVAR method obviating the need for open heart surgery. Conclusion Endovascular repair of aneurysms in post-coarctoplasty patients is a promising method and should be considered in those with suitable anatomy based on prior imaging.